2021
DOI: 10.1002/ardp.202100190
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxybenzoic acid derivatives as potential new antimalarial agents

Abstract: With more than 200 million cases and 400,000 related deaths, malaria remains one of the deadliest infectious diseases of 2021. Unfortunately, despite the availability of efficient treatments, we have observed an increase in people infected with malaria since 2015 (from 211 million in 2015 to 229 million in 2019). This trend could partially be due to the development of resistance to all the current drugs. Therefore, there is an urgent need for new alternatives. We have, thus, selected common natural scaffolds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…This could confirm the major role of the phenolic hydroxyl groups, as discussed before, and the intramolecular bonds in the aqueous solubility. 16…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This could confirm the major role of the phenolic hydroxyl groups, as discussed before, and the intramolecular bonds in the aqueous solubility. 16…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in contrast to their corresponding monomers (8,(44)(45), in which only 8 was active on Plasmodium, all the dimers exhibited an equivalent antiplasmodial efficacy. 16 Therefore, the dimer is equally potent, even if the scaffold possesses a 3,4-or 3,5-dihydroxybenzoate moiety. This suggested that the dimerization of these structures created new beneficial interactions with the targets since this effect was not the result of the cumulative activity of two polyhydroxybenzoic acid molecules but instead of one.…”
Section: Rsc Medicinal Chemistry Research Articlementioning
confidence: 99%
See 3 more Smart Citations